Perceptions of undergraduate student nurses on e-learning at University of Namibia Main Campus, Windhoek: a lesson learnt from the COVID-19 pandemic - Nepembe, Maria N. N.; Amakali-Nauiseb, Taimi; Emvula, Olivia (International Journal Of Community Medicine And Public Health, 2023)
The aim of the study was to explore and describe the perceptions of second year nursing degree student’s academic performance through e-learning during COVID-19 pandemic at University of Namibia Main Campus, Windhoek. A qualitative research design was adopted and a total number of sixteen (16) second-year nursing students were interviewed. An interview guide, an audio recorder and field notes were used as the data collection instruments. Convenience, purposive sampling was employed. Key themes which emerged from the study were: Student nurse’s perceptions regarding their e-learning experience; Student nurse’s perceptions regarding the availability of studying and learning resources such as gadgets and internet, Student nurses’ perceptions of the e-learning environment. The study revealed that student nurses during e-learning were negatively affected by many factors, such as lack of electronic resources (laptops, smart phones), low phone storage to download big files, slow internet connections/poor network coverage for telecom network (TN) in some areas, limited internet data (TN mobile 10 GB) provided by the institution monthly, limited time to complete online assessment, less effort from lecturers (dropping notes on the forum and not teaching compared to face-to-face learning), workload at home doing house chores and not excused for online lessons, living in remote areas with no electricity, cheating of students during online tests and assessments. The study recommends an increased in the amount of internet for telecom network (TN mobile) data provided monthly by the institution, lecturers to give sufficient time to complete online tests and assessments, and to develop a system that detects cheating.